Private sector participation in infrastructure: Can the price of risk transfer be efficient? - Dejan Makovšek; Marian Moszoro (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
There is a drive towards delivering and operating public infrastructure through public-private partnerships as opposed to traditional approaches. The assessment of the value for money achieved by the two alternative approaches rests on both the cost of financing, and the efficiency in delivery and operation. This paper focuses on the cost of financing, and in particular the cost associated with transferring risk from the public to private sphere. If capital markets are efficient and complete, the cost of private and public financing should be the same, with the relative delivery and operational efficiency remaining as the primary determinant of value for money. However, evidence suggests the risk transfer to a public-private partnership entails an inefficient risk pricing premium. We argue that a high price for public-private partnerships results from large risk transfers, risk treatment within the private sector, and uncertainty around the past and future performance of PPP consortiums. The corollary of the finding is that the efficiency gains from a PPP need to be much higher than previously understood to deliver better value for money than under a traditional approach.
Keywords: 330; Verkehrsinfrastruktur; Infrastrukturinvestition; Öffentlich-private Partnerschaft; Investitionsrisiko; Risikoprämie